The Triumph of Morality in William Shakespeare’s King Lear: An Analysis from the Qur’anic Perspective - Saeed, Asmaa Mukaram (Al-Adab Journal, 2022)
A set of relationships governs the kind of communications among people within one or more societies, of which most important is the one that occurs between children and their parents, especially fathers. Psychologically speaking, this kind of relationship is so significant insofar as it is the basis of the child’s personality inasmuch as it is the source of its character and action in social media. Undoubtedly, the most significant factor in a drama is the social relationships among which child-father relationship is a recurring theme. William Shakespeare appears to be much more occupied in this sort of relationship which prominently and significantly figures out in most of his dramas such as Romeo and Juliet, Titus Andronicus and Hamlet. Most important is the child-relationship in King Lear. In Shakespeare’s plays children and parents interact in various ways, for they are headed to behave in such a way that leads to the resolution he intends to cite at the end of the play. As in life, conflicts among the family members that appear in his drama are very important whether resolved or not. This paper mainly revolves around the child-father relationship in King Lear, especially the one between Lear’s daughters Goneril, Regan and Cordelia on the one hand, and their father on the other; and between Edmund and his father Gloucester as far as the theme of ingratitude is concerned. Many studies have been made on the filial relationships in this play, which have at the same time ignored the close relationship between the Qur’anic connotations attained by the dramatist and the essential themes in this play. To attempt such a study like this is to shed light on Shakespeare’s awareness of the Islamic representations reflected in King Lear as far as the theme of ingratitude is concerned. Many attempts have been made to analyze Shakespeare’s drama from the Islamic perspective; yet, this play has not got its due analysis from the Islamic viewpoints. This paper is to clearly view the themes of ingratitude, the children-father relationship, adultery, injustice, foolish behavior and brotherly relationships in terms of the relevant Islamic representations. When considering all the complications that surround the environment of the play it is recognized that the morality as reflected in the Holy Qur’an triumphs over evil powers and any other representations contrary to it.